The Role of Economic Value in Mediating the Influence of Price Perception on Students’ Decisions to Use Maxim Bike Services : JEL Classification: D12, L84, M31, R41, C12 - Sugianto Sugianto; Ariyanti Inayah; Andi Sugeng Sapta Aji; Hasmawati Hasmawati; Hasriani Hasriani (Newinera Publisher, 2026)
This study analyzes the role of economic value in mediating the influence of price perception on students’ decisions to use Maxim Bike services at STIE Indonesia Makassar. A quantitative approach with a descriptive verificative design was employed. The study involved 50 active students who had used Maxim Bike services. Data were collected through a questionnaire using a 1 to 5 Likert scale and analyzed using Structural Equation Modeling with AMOS 24. The findings show that all indicators were valid, with loading factor values above 0.70. Reliability testing also confirmed that all variables were reliable, with Cronbach’s Alpha values ranging from 0.86 to 0.88 and Composite Reliability values ranging from 0.88 to 0.90. Descriptive analysis indicated that price perception, economic value, and service use decision were relatively high, with mean values above 3.4. The mediation test revealed that economic value partially mediated the relationship between price perception and service use decision, with an indirect effect of 0.49, CR of 6.13, and p < 0.001. The model also met the goodness of fit criteria, with Chi-square/df = 1.95, CFI = 0.96, TLI = 0.95, RMSEA = 0.055, and SRMR = 0.048.These findings indicate that economic value plays an important mediating role in strengthening the effect of price perception on students’ decisions to use Maxim Bike services. Therefore, Maxim Bike management should maintain competitive pricing while improving perceived service value.